Relação da incontinência urinária e depressão no idoso entre faixas etárias - Oliveira, Luisa Bonini de [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Objetivos: Analisar a relação da incontinência urinária (IU) com a depressão em idosos por faixa etária. Além disso, foi verificada se há diferença na IU e na depressão entre faixas etárias. Métodos: As avaliações foram feitas em 164 idosos moradores da comunidade por meio de três questionários: Geriatric Depression Scale-15 (GDS-15), International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) e Incontinence Severity Index (ISI) que avaliaram a depressão e a IU, respectivamente. Resultados: Foi observada correlação entre os escores da GDS-15 e o ICIQ-SF nas faixas etárias 70-79 anos (r = 0,382; p = 0,001) e ≥ 80 anos (r = 0,403; p = 0,002). Houve efeito da idade na IU-ISI [2(2) = 12,457 (p = 0,002)], mas não na GDS-15 e no ICIC-SF. Conclusão: houve correlação entre IU e depressão em idosos nas faixas etárias de 70-79 anos e de ≥80 anos. Também houve interferência da idade na ocorrência da IU.

Objectives: Analyse the relationship between urinary incontinence (UI) and depression within the elderly through age groups. In addition, it was verified whether there is a difference in UI and depression between age groups. Methods: Assessments were carried out on 164 elderly people living in the community using three questionnaires: Geriatric Depression Scale-15 (GDS-15), International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) and Incontinence Severity Index (ISI) which evaluated depression and UI, respectively. Results: A correlation between the GDS-15 scores and the ICIQ-SF in the age groups 70-79 years (r = 0.382; p = 0.001) and ≥ 80 years (r = 0.403; p = 0.002) was pointed out. There was consequences of age on the UI-ISI [χ2(2) = 12.457 (p = 0.002)], but not on the GDS-15 and ICIC-SF. Conclusion: there was a correlation between UI and depression in the elderly aged 70-79 years and ≥80 years. Age also interfered in the occurrence of UI.
Relationship of urinary incontinence and depression in the elderly between age groups
Keywords: Incontinência urinária; Depressão; Isolamento social; Envelhecimento; Urinary incontinence; Depression; Social isolation; Aging